Global justice a cosmopolitan account - Brock, Gillian (Oxford : Oxford University Press, 2009)
Gillian Brock develops a model of global justice that takes seriously the moral equality of all human beings notwithstanding their legitimate diverse identifications and affiliations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social justice; Cosmopolitanism